Google apps script : exercise coding projects. (Packt Publishing, 2022)
Bring your coding to the next level or get more familiar with all the amazing things that can be done with Google Apps Script. About This Video Learn to create bound applications that allow you to use the Google Workspace container and create customized interactions within it Expand your Google Workspace knowledge with exercises and challenges Learn to connect various Google Workspace services to create applications In Detail Google Apps Script is by far one of the best coding languages to get started with, as it allows you to access the power of all the Google services that simply work so incredibly well within the script. It is based on JavaScript, which makes it easy to get started. You will start by learning how to write code in Google Apps Script and understand the features of Google Apps Script. You will learn to create projects and open the project to update and edit the code. Moving on, you will learn how to use the power of the Workspace services and create custom macros adding advanced functions to your spreadsheet with Google Apps Script. You will understand how to interact with Google Workspace services, see examples of using Classes in Workspace services, and learn how to access class methods. Then we will explore some amazing applications that can be built with Google Apps Script. The projects of this course will demonstrate how to apply Google Apps Script code to create docs, create a web app with both GET and POST endpoints, make use of sheet data, get sheet data, send emails, and much more. We will wrap up the course by creating a web form that can send emails using your Gmail account. By the end of the course, you will learn to interact with Google Workspace services and learn how to code Google Apps Script. Audience This course is for Google Workspace users, web developers, and web designers. It can also be taken by application developers who want to learn Apps Script, Google Workspace users who want advanced and customized functionality, and JavaScript developers who want to learn Apps Script. This course is also useful to anyone who uses Google Workspace and wants custom functionality for Google Workspace users. All you need is an internet connection and a Google Account, and you can start creating your coding apps.